A Single Phase Hybrid Active Power Filter Using Unified Constant-Frequency Integration Control - Nur Huda, Ramlan; Naziha, Ahmad Azli; Hanifah, Jambari (2014)
This paper proposes a single-phase hybrid active power filtering using Unified Constant-Frequency Integration (UCFI) as the controller. The proposed topology interconnects the passive filter with shunt active power filter through point of common coupling (PCC). The topology chosen for active power filtering is a cascaded H-bridge multilevel inverter (CHMI) which offers wide range of advantages over basic configuration of active power filter. The hybrid topology provides advantages over non-hybrid active filter which is able to compensate both higher and lower order of harmonics. This paper describes the multilevel inverter circuit topology, passive filter design to be incorporated with the shunt active power filter (APF) and the implementation of UCFI control scheme. The system is verified using MATLAB/Simulink. Comparison analysis shows the performance evaluation of each compensation circuit from basic H-bridge inverter circuit to non-hybrid multilevel inverter circuit and the proposed hybrid configuration. Simulation results shows that the total harmonic distortion of the source current have been reduce abruptly from 125.53% to 3.47% after compensation using the proposed hybrid configuration.